2007
DOI: 10.1007/s10620-006-9560-z
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Low-Regulatory CD25High+CD4+ and High-Pro-inflammatory CD28−CD4+ T-Cell Subsets in Patients with Ulcerative Colitis: Modified by Selective Granulocyte and Monocyte Adsorption Apheresis

Abstract: Low-CD25(High+)CD4(+), a subset of regulatory CD25(+)CD4(+) T cells and high-inflammatory CD28(-)CD4(+) T cells can exacerbate ulcerative colitis (UC). This study sought to investigate the frequency of CD25(High+)CD4(+) and CD28(-)CD4(+) T cells in patients with UC and the changes in these cells during Adacolumn granulocyte and monocyte adsorption apheresis (GMA). Subjects were 12 patients with active UC, 11 with quiescent UC, and 14 healthy volunteers (HVs). The mean clinical activity index was 15.7 +/- 2.2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 49 publications
2
48
2
Order By: Relevance
“…Their observations suggested that the Adacolumn not only selectively removes neutrophils and monocytes from the circulation but also indirectly promotes expansion of Bregs, which are involved in maintaining regulatory T cells (Tregs) [31,32]. In clinical settings, the Adacolumn has been associated with the expansion of Tregs and an increase in interleukin-10 level [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Their observations suggested that the Adacolumn not only selectively removes neutrophils and monocytes from the circulation but also indirectly promotes expansion of Bregs, which are involved in maintaining regulatory T cells (Tregs) [31,32]. In clinical settings, the Adacolumn has been associated with the expansion of Tregs and an increase in interleukin-10 level [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on the knowledge that within the lymphocyte population certain T cell subsets are major factors in the immune pathology of intestinal mucosa, while other subsets are essential regulators, controlling IBD [57], we were looking for any relationship between factors associated with skewed TCR repertoire and the UC disease, together with a special interest in the role of bacterial SA in any prevailing T cell behaviour. There was no significant correlation between the percentage frequency of TCRBV4 and CAI.…”
Section: Discussionmentioning
confidence: 99%
“…+ cells may be persistent up to 10 weeks after treatment [21][22][23]. In our study we did not capture the precise duration of the increase in blood Treg.…”
Section: /Foxp3mentioning
confidence: 97%